SLC22A4 Gene in Hereditary Non-syndromic Hearing Loss: Recurrence and Incomplete Penetrance of the p.C113Y Mutation in Northwest Africa - Chiereghin, Chiara; Robusto, Michela; Mauri, Lucia; Primignani, Paola; Castorina, Pierangela; Ambrosetti, Umberto; Duga, Stefano; Asselta, Rosanna; Soldà, Giulia (Frontiers in Genetics, 2021)
Inherited hearing loss is extremely heterogeneous both clinically and genetically. In addition, the spectrum of deafness-causing genetic variants differs greatly among geographical areas and ethnicities. The identification of the causal mutation in affected families allows early diagnosis, clinical follow-up, and genetic counseling. A large consanguineous family of Moroccan origin affected by autosomal recessive sensorineural hearing loss (ARSNHL) was subjected to genome-wide linkage analysis and exome sequencing. Exome-wide variant analysis and prioritization identified the SLC22A4 p.C113Y missense variant (rs768484124) as the most likely cause of ARSNHL in the family, falling within the unique significant (LOD-score>3) linkage region on chromosome 5. Indeed, the same variant was previously reported in two Tunisian ARSNHL pedigrees. The variant is present in the homozygous state in all six affected individuals, but also in one normal-hearing sibling, suggesting incomplete penetrance. The mutation is absent in about 1,000 individuals from the Greater Middle East Variome study cohort, including individuals from the North African population, as well as in additional seven deaf patients from the same geographical area, recruited and screened for mutations in the SLC22A4 gene. This study represents the first independent replication of the involvement of SLC22A4 in ARSNHL, highlighting the importance of the gene, and of the p.C113Y mutation, at least in the Northwest African population.